2003
DOI: 10.1590/s0100-204x2003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da vitamina C no ganho de peso e em parâmetros hematológicos de tambaqui

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da suplementação dietária com ácido L-ascórbico (vitamina C) no ganho de peso e em parâmetros hematológicos de juvenis de tambaqui, Colossoma macropomum. Após dez semanas, em que foram alimentados com dietas contendo 0, 100 e 500 mg de ácido L-ascórbico por kg de ração, os peixes foram capturados e imediatamente anestesiados para a coleta de sangue da veia caudal e determinação dos parâmetros hematológicos. Animais alimentados com maiores níveis de ascorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 18 publications
6
19
0
7
Order By: Relevance
“…The data obtained by Chagas et al (2007) when they evaluated different feeding rates (1.0, 3.0 and 5.0) for tambaqui (Colossoma macropomum) reared in net cages revealed higher averages (P<0.05) of weight gain for fish subjected to the rate of 3.0 and 5.0% feeding when compared with animals subjected to 1.0% feeding. On the other hand, the authors described that the best results of apparent feed conversion (AFC) were obtained with fish under 1.0% feeding, for at 3.0 and 5.0%, the AFC indices found were 4.86 and 7.07, respectively, and these values are superior to those of the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained by Chagas et al (2007) when they evaluated different feeding rates (1.0, 3.0 and 5.0) for tambaqui (Colossoma macropomum) reared in net cages revealed higher averages (P<0.05) of weight gain for fish subjected to the rate of 3.0 and 5.0% feeding when compared with animals subjected to 1.0% feeding. On the other hand, the authors described that the best results of apparent feed conversion (AFC) were obtained with fish under 1.0% feeding, for at 3.0 and 5.0%, the AFC indices found were 4.86 and 7.07, respectively, and these values are superior to those of the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Their results in common carp (Cyprinus carpio) showed that a normal versus high ascorbate intake did not influence the physiological stress indicators, such plasma cortisol, not supporting the hypothesis that high concentration of ascorbate would inhibit steroidogenesis. The vitamin C requirements of matrinxã is not yet established, but the doses tested were within the range determined for other native species: 139 mg kg.ration -1 for pacú (Piaractus mesopotamicus) (Martins, 1995), 25 mg kg.ration -1 for acará (Astronotus ocellatus) (Fracalossi et al, 1998) and 100 mg kg.ration -1 for tambaqui (Colossoma macropomum) (Chagas & Val, 2003).…”
mentioning
confidence: 76%
“…The levels of vitamin tested were established according to previous studies with native fish (Martins, 1995;Fracalossi, 1998;Chagas and Val, 2003). Ascorbyl polyphosphate (Stay C 35, Roche) was the source of vitamin C.…”
Section: Methodsmentioning
confidence: 99%
“…Foram determinadas as exigências nutricionais do tambaqui quanto aos macro e micronutrientes em diferentes fases de vida (MACEDO-VIEGAS et al, 1996;CHAGAS & VAL, 2003); contudo, existem poucas informações sobre sua taxa de alimentação e freqüência de arraçoamento em criação intensiva.…”
Section: Introductionunclassified